Infodemic in Public health a reemerging public health threat: a scoping review [version 1; peer review: 2 approved] - Aishwarya Shodhan Shetty; Mithun Pai; Shweta Yellapurkar (F1000Research, 2023)
Background: Infodemic is a neologism of ‘information’ and ‘epidemic’ coined in the year 2003. Evidence mapping is a technique to appraise the literature which enables the extent of research activity in a specific area to be discovered. The main objective of this evidence synthesis presents the outcomes of an evidence map that was directed to know the extent of Infodemics and its effects on public health.  Methods: The following methods were used to construct this evidence synthesis: Phase I. Construct a Broad Question Referring to the Field of Analysis. Phase II; Defining Key Variables to Be Mapped, identifying the characters of each variable and Outline Inclusion and Exclusion Criteria for the variables. Phase III: Literature search. Phase IV: Screening and Charting the Appropriate Evidence within the Synthesis.  Results:  Authors identified 55 records through database searching, after screening for duplicates, 53 records screened at title/abstract level of which, 16 records were removed because of lack of complete article or articles were not in English. 37 articles were eligible for full text screening, 37 full-text articles were than assessed for eligibility and only 22 articles were included as per inclusion criteria with an interrater Outcome Kappa value: 0.91. The strength of agreement was considered to be 'excellent'.  Conclusions: This synthesis focused majorly on the gaps in the research focused on infodemic. The two main gaps identified were lack of systematically conducted research and poor digital health literacy. As infodemic is a new phenomenon with respect to the COVID-19 pandemic it was an eye opener at different levels of public health, furthermore this evidence map points out areas for further research on the impact of infodemic.